Survival of Staphylococcus aureus ST398 in the Human Nose after Artificial Inoculation - Slingerland, Bibi C. G. C. (Public Library of Science, 2012)
There is evidence that MRSA ST398 of animal origin is only capable of temporarily occupying the human nose, and it is therefore, often considered a poor human colonizer. We inoculated 16 healthy human volunteers with a mixture of the human MSSA strain 1036 (ST931, CC8) and the bovine MSSA strain 5062 (ST398, CC398), 7 weeks after a treatment with mupirocin and chlorhexidine-containing soap. Bacterial survival was studied by follow-up cultures over 21 days. The human strain 1036 was eliminated faster (median 14 days; range 2–21 days) than the bovine strain 5062 (median 21 days; range 7–21 days) but this difference was not significant (p = 0.065). The bacterial loads were significantly higher for the bovine strain on day 7 and day 21. 4/14 volunteers (28.6%) showed elimination of both strains within 21 days. Of the 10 remaining volunteers, 5 showed no differences in bacterial counts between both strains, and in the other 5 the ST398 strain far outnumbered the human S. aureus strain. Within the 21 days of follow-up, neither human strain 1036 nor bovine strain 5062 appeared to acquire or lose any mobile genetic elements. In conclusion, S. aureus ST398 strain 5062 is capable of adequately competing for a niche with a human strain and survives in the human nose for at least 21 days.